No ar...As (in) certezas da comunicação nas rádios comunitárias em catalão-goiás (1992 2011) - (:unkn) unknown (Universidade Federal de Goiás, 2011)
The debate on media, in general forms and public media, radio licenses and TVs, in a specific way, it s on our country s day order, mainly because the National Conference on Communication has recently happened, and it has showed the extreme necessity and immediacy of discussing the means of public licenses distribution, which has risen ideas and values that demonstrate the importance of this debate to the democratization of the access to information in Brazil. Therefore, the communitarian radios emerged like a tool to the construction of both citizenship and democratic expression from social movements initiatives such as trade union, student activism and neighborhood associations, expressions from the modern world that are worth a more specific study. In Catalão/GO there are some initiatives in creating and establishing communitarian radios; specifically two has developed and were able to receive from the Ministry of Communications the appropriate license to work: Rádio Laser FM, in the district of Ipanema and Rádio Athenas FM, in the district of Castelo Branco. Both radios broadcast their programs and fully enjoy the law which has legalized the communitarian radio broadcast service in Brazil. This paper aims to deeper understand this law, its guidelines and implications, the mechanisms that make those radios effectively communitarian and the bias by which the respective communitarian association directories has engaged for the means of their survival. In the same way, it s analyzed if the show is really being broadcasted through the schedules of two stations, the broadcasted programmes and their impact in the community. Also, a diagnosis for the problem of communitarian communication in Catalão is built, including its difficulties and its main problems with the 1962 s law, which institutes the communitarian radio broadcast service and develop solutions for this situation.
The air ...The (un) certainties of communication in community radio stations in Catalan-goiás (1992 - 2011)
Keywords: Catalão; comunicação; rádio comunitária; movimentos sociais.; Catalão; communication; communitarian radio; social movement; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA